2018
DOI: 10.1016/j.erss.2018.05.019
|View full text |Cite
|
Sign up to set email alerts
|

To climb or not to climb? Investigating energy use behaviour among Solar Home System adopters through energy ladder and social practice lens

Abstract: Solar Home Systems (SHSs) and other off-grid solutions have shown promise in addressing the energy access gap for those with no or unreliable grid services. With that promise comes the expectation to boost socioeconomic well-being of newly-connected households, who will continue climbing up the energy ladder. Despite the growing appreciation for the need to go beyond the techno-economics of energy access, and the recognition of the value of socio-technical systems perspective, the wider sociology of energy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 49 publications
0
49
0
Order By: Relevance
“…For example, cultural clashes between ideas of possession vs. ownership were observed to make repossession of PAYG equipment in the event of default difficult, especially where customers were accustomed to free handouts from past development projects. Fluctuations in income and ability to top up payment plans due to the nature of customers' livelihoods were also noted (e.g., agricultural incomes, or highly-mobile market traders-the former also being noted by Bisaga and Parikh [18]). This inflexibility towards seasonal incomes potentially undermines Rolffs et al's [8] point on the close match between PAYG payment plans and existing consumer practices around paying for energy.…”
Section: Socio-cultural Dimensions Of Paygmentioning
confidence: 96%
See 4 more Smart Citations
“…For example, cultural clashes between ideas of possession vs. ownership were observed to make repossession of PAYG equipment in the event of default difficult, especially where customers were accustomed to free handouts from past development projects. Fluctuations in income and ability to top up payment plans due to the nature of customers' livelihoods were also noted (e.g., agricultural incomes, or highly-mobile market traders-the former also being noted by Bisaga and Parikh [18]). This inflexibility towards seasonal incomes potentially undermines Rolffs et al's [8] point on the close match between PAYG payment plans and existing consumer practices around paying for energy.…”
Section: Socio-cultural Dimensions Of Paygmentioning
confidence: 96%
“…As inferred above, the existing literature is at best patchy and a long way from providing any comprehensive overview of what is a rapidly expanding and metamorphosing phenomenon. A literature search using Scopus, Web of Science, Science Direct, and Google Scholar, together with direct approaches to authors of some of the papers these searches identified to ask if they were aware of other literature we had missed, resulted in identification of only five articles in mainstream academic journals [8,9,12,18,19], seven articles in practitioner journals [20][21][22][23][24][25][26], and six detailed reports [5,7,10,11,27,28]. Of these latter, three were produced by the global mobile operators' key trade association (the GSMA) [7,11,27], one by researchers from UC Berkeley based on a study commissioned by the World Bank [10], one by the World Resources Institute [5], and one by an independent think tank, the Consultative Group to Assist the Poor [28].…”
Section: Coverage Of Existing Literaturementioning
confidence: 99%
See 3 more Smart Citations